2013
DOI: 10.1111/lang.12009
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Gender, and Possible Selves

Abstract: [This is the pre-publication version of Henry, A. (2013) The motivational effects of crosslinguistic awareness: Developing third language pedagogies to address the negative impact of the L2 on the L3 self-concept. Innovations in Language Learning and Teaching DOI:10.1080/17501229.2012.733008] ] IntroductionThe last fifteen years have seen a burgeoning research interest in multilingualism witnessed, the recent yet nevertheless fundamental recognition that humans are "potentially multilingual by nature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 52 publications
3
73
2
Order By: Relevance
“…The findings regarding the ideal L2 self, or an image of oneself as a proficient speaker of an L2 (Dörnyei, ), are conflicting. Female learners have reported more robust visions of themselves as successful language users than their male peers in the studies looking at Japanese learners of English (Ryan, ) and Swedish L3 learners of German, French and Spanish (Henry & Cliffordson, ). Henry and Cliffordson () propose that the reason for this difference is that females are more likely than males to construct interdependent selves, which stress interaction with others, leading to more robust ideal L2 selves.…”
Section: Motivation and Gender Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings regarding the ideal L2 self, or an image of oneself as a proficient speaker of an L2 (Dörnyei, ), are conflicting. Female learners have reported more robust visions of themselves as successful language users than their male peers in the studies looking at Japanese learners of English (Ryan, ) and Swedish L3 learners of German, French and Spanish (Henry & Cliffordson, ). Henry and Cliffordson () propose that the reason for this difference is that females are more likely than males to construct interdependent selves, which stress interaction with others, leading to more robust ideal L2 selves.…”
Section: Motivation and Gender Differencesmentioning
confidence: 99%
“…These studies concluded that female learners are more highly motivated than their male colleagues. However, a small number of studies reported lack of such differences (Henry & Cliffordson, ; Sylvén & Thompson, ). There might be a number of reasons for these conflicting results, for example Kissau and Turnbull () review a number of studies that reveal that male learners perceive certain languages as more ‘feminine’ than others.…”
Section: Introductionmentioning
confidence: 99%
“…While the proportion believing that they learnt equally much English as a result of school work as they did outside school was roughly similar (girls 35%, boys 33%), striking differences can be seen in the categories 'learn most of my English outside school' (girls 8%, boys 14%) and 'learn all, or nearly all of my English outside school' (girls 3%, boys 6%). Given that in a recent study Henry and Cliffordson (2013) failed to find any gender-related differences in Swedish 9 th grade students' ideal English-speaking/using selves, the rather dramatic divergences in students' beliefs about learning English warrant further investigation. In the sections that follow the theories previously discussed are revisited, this time considering whether gender-related differences generally found in self-efficacy, attribution and self-theory research have the potential to shed light on differences in girls' and boys' beliefs about learning English.…”
Section: Gender Differences In Beliefs About Learning Englishmentioning
confidence: 85%
“…Thus, although there is no general agreement on this as yet, female students are mostly reported to have more positive language learning attitudes and be more strongly motivated than male students (Merisuo-Storm 2007 ;Pavlenko and Piller 2008 ), although such differences have not always proved signifi cant (Weseley 2012 ;Henry and Cliffordson 2013 ).…”
Section: Clil and Affectivitymentioning
confidence: 87%